Natural rubber latex-based biomaterials for drug delivery and regenerative medicine: Trends and directions - Marques, Paulo Augusto Chagas; Guerra, Nayrim Brizuela [UNESP]; dos Santos, Lindomar Soares; Mussagy, Cassamo Ussemane; Pegorin Brasil, Giovana Sant'Ana [UNESP]; Burd, Betina Sayeg [UNESP]; Su, Yanjin [UNESP]; da Silva Sasaki, Josana Carla [UNESP]; Scontri, Mateus [UNESP]; de Lima Lopes Filho, Paulo Eduardo [UNESP]; Silva, Glaucio Ribeiro; Miranda, Matheus Carlos Romeiro; et al. (Elsevier, 2024)
Natural Rubber Latex (NRL) has shown to be a promising biomaterial for use as a drug delivery system to release various bioactive compounds. It is cost-effective, easy to handle, biocompatible, and exhibits pro-angiogenic and pro-healing properties for both soft and hard tissues. NRL releases compounds following burst and sustained release kinetics, exhibiting first-order release kinetics. Moreover, its pore density can be adjusted for tailored kinetics profiles. In addition, biotechnological applications of NRL in amblyopia, smart mattresses, and neovaginoplasty have demonstrated success. This comprehensive review explores NRL's diverse applications in biotechnology and biomedicine, addressing challenges in translating research into clinical practice. Organized into eight sections, the review emphasizes NRL's potential in wound healing, drug delivery, and metallic nanoparticle synthesis. It also addresses the challenges in enhancing NRL's physical properties and discusses its interactions with the human immune system. Furthermore, examines NRL's potential in creating wearable medical devices and biosensors for neurological disorders. To fully explore NRL's potential in addressing important medical conditions, we emphasize throughout this review the importance of interdisciplinary research and collaboration. In conclusion, this review advances our understanding of NRL's role in biomedical and biotechnological applications, offering insights into its diverse applications and promising opportunities for future development.
Keywords: Controlled release; Drug delivery; Nanoparticles; Natural rubber latex; Regenerative medicine; Wound healing